COVID-19 vaccine hesitancy among people living with HIV in a low-resource setting: A multi-center study of prevalence, correlates and reasons. Issue 15 (6th April 2023) - Kabir Sulaiman, Sahabi; Sale Musa, Muhammad; Isma'il Tsiga-Ahmed, Fatimah; Muhammad Dayyab, Farouq; Kabir Sulaiman, Abdulwahab; Dabo, Bashir; Idris Ahmad, Saidu; Abubakar Haruna, Salisu; Abdurrahman Zubair, Abdullahi; Hussein, Aminu; Usman, Sadiya; Usman Wada, Jummai; et al.
Highlights: Approximately 13% of the study participants have received at least one dose of the COVID-19 vaccine. Nearly six in ten unvaccinated participants were hesitant to accept the COVID-19 vaccine. Age ≥50 years, unemployment, and past ART adverse reaction are associated with lower odds of hesitancy. Females and those attending ART clinics located in the states' capitals have higher odds of hesitancy. Major reasons for COVID-19 vaccine hesitancy included fear of adverse effects and doubts about the vaccine's efficacy. Abstract: Background: Hesitancy to COVID-19 vaccine may worsen the burden of COVID-19 among people living with HIV (PLHIV), who are at a higher risk of COVID-19-related hospitalization and death, compared to HIV non-infected individuals. Therefore, we evaluate the predictors and reasons for COVID-19 vaccine hesitancy among unvaccinated PLHIV in six antiretroviral therapy (ART) clinics across northern Nigeria. Methodology: In this cross-sectional study, conducted between October 2021 and February 2022 in six hospitals across two geopolitical regions of Nigeria, we utilized interviewer-administered questionnaires to assess COVID-19 vaccine hesitancy among a convenience sample of 790 eligible adult PLHIV. Hesitancy was defined as answering 'no' or 'maybe' to a question asking participants their willingness to accept the COVID-19 vaccine. A multivariate logistic regression model was used to estimate the adjusted odds ratio (aOR) and 95% confidence interval (CI) of the factors associated with COVID-19 vaccine hesitancy among PLHIV. Results: Of the total 660 unvaccinated participants included in the analysis (61.82% female, mean age [SD] of 39.76 [10.75]), 381 (57.72%) were hesitant to COVID-19 vaccine. Being 50 years and older (aOR: 0.43; 95% CI: 0.21–0.89), being unemployed (aOR: 0.57; 95% CI: 0.34–0.95), experiencing the adverse effects of ART (aOR: 0.36; 95% CI: 0.15–0.86), and perception of being at high risk of contracting COVID-19 (aOR: 0.22; 95% CI: 0.13–0.37) were associated with significantly lower odds of hesitancy. Conversely, being female (aOR: 1.64; 95% CI: 1.02–2.61) and attending ART clinics at state administrative capital cities (IIDH Kano [aOR: 2.40; 95% CI: 1.10–5.25], MMSH Kano [aOR: 5.59; 95% CI: 1.97–10.66], YSSH Damaturu [aOR: 9.88; 95% CI: 4.02–24.29] vs. GH Gashua) were associated with significantly higher odds of hesitancy. The most common reasons for hesitancy include fear of potential adverse effects, skepticism about vaccine efficacy, the rapid development of the COVID-19 vaccine, and the perceived lack of effort to develop a cure or vaccine for HIV/AIDS. Conclusion: Interventions aimed at combating misperceptions and misinformation regarding the COVID-19 vaccination program may reduce the prevalence of COVID-19 vaccine hesitancy among unvaccinated PLHIV.